Exploring the Impact of First Mile/Last Mile Solutions on Traffic Congestion and Air Quality in Urban Areas - Yimeng Li (Studies in Social Science & Humanities, 2023)
Ride-hailing and bike-sharing have gained popularity as first-mile/last-mile solutions in urban areas, as these services can improve the efficiency and sustainability of urban transport systems. However, they can also affect traffic congestion and air quality. This paper examines the impact of different first-mile/last-mile solutions for ride-hailing and shared bikes on traffic congestion and air quality in urban areas. Shared bikes are considered an effective solution to reduce vehicle mileage and improve air quality. Several studies have found that shared bike systems have great potential to reduce traffic congestion and emissions. The paper also uses population density and land models to demonstrate the effectiveness of the proposal, illustrating the availability of alternative modes such as public transport or walking and cycling infrastructure.